Análise das linhas de crédito do plano ABC+ para agricultura familiar - Júnia Cristina Péres Rodrigues da Conceiç\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The work sought to analyze the performance of the credit lines, present in the ABC+ Plan for family farming, checking how this insertion of family farming in the ABC+ Plan is going, specifically, how the credit lines, contained in the ABC+ Plan, are operating, aimed at family farmers. To this end, a literature review was carried out on the subject and, based on data from the rural credit manual (MCR), it was verified how the credit lines intended for family farmers, included in the ABC+ plan, are behaving: Pronaf ABC+ Bioeconomy, Pronaf ABC+ Agroecology, Pronaf ABC+ Forests and Pronaf ABC+ Semiarid. The results found indicate that the participation of these credit lines is small in relation to the total Pronaf. Credit, although important, has not been sufficient to promote low-carbon family farming. That is, credit from the Pronaf ABC+ subprograms, intended for the adoption of sustainable practices by family farming, are not being demanded, the number of contracts and the volume of credit are small, when compared to the volume and number of Pronaf contracts.
Keywords: Q1; Q15; 330; ABC+ Plan; Pronaf credit; sustainability; family agricultural